Using community-based evidence for decentralized health planning: insights from Maharashtra, India. Issue 1 (22nd September 2014) - Shukla, Abhay; Khanna, Renu; Jadhav, Nitin
Abstract: Health planning is generally considered a technical subject, primarily the domain of health officials with minimal involvement of community representatives. The National Rural Health Mission launched in India in 2005 recognized this gap and mandated mechanisms for decentralized health planning. However, since planning develops in the context of highly unequal power relations, formal spaces for participation are necessary but not sufficient. Hence a project on capacity building for decentralized health planning was implemented in selected districts of Maharashtra, India during 2010–13. This process developed on the platform of officially supported community-based monitoring and planning, a process for community feedback and participation towards health system change. A specific project on capacity building for decentralized planning included a structured learning course and workshops for major stakeholders. An evaluation of the project, including in-depth interviews of various participants and analysis of change in local health planning processes, revealed positive changes in intervention areas, including increased capacity of key stakeholders leading to preparation of evidence-based, innovative planning proposals, significant community oriented changes in utilization of health facility funds, and inclusion of community-based proposals in village, health facility-based block and district plans. Transparency related to planning increased along with responsiveness of health providers to community suggestions. A key lesson is that active facilitation of decentralized health planning and influencing the health system to expand participation, are essential to ensure changes in planning. Effective strategies included: identifying people's health service related priorities through community-based monitoring, capacity building of diverse stakeholders regarding local health planning, and advocacy to enable participation of community-based actors in the planning process. This combination of strategies draws upon the framework of 'empowered participatory governance' which necessitates combining a degree of 'countervailing power' and acceptance of participation by the system, for new forms of governance to emerge.